Opioid Medication Errors in Pediatric Practice: Four years’ Experience of Voluntary Safety Reporting - Conor Mc Donnell (Pain Research and Management)
BACKGROUND: Opioids are the most common source of drug error that leads to harm in pediatric hospitals.